2015
DOI: 10.1007/s11356-015-5783-x
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the anthropogenic impact in the Augusta Harbor (Eastern Sicily, Italy) in the last decades: benthic foraminifera as indicators of environmental status

Abstract: The study of benthic foraminifera in sediment cores provides the opportunity to recognize environmental changes, including those due to the anthropogenic impact. The integration of these data with chemical-physical parameters provides a comprehensive quality assessment. This research was applied to a sediment core collected in the Augusta bay, where a very large commercial and military harbor and one of the largest petrochemical poles in Europe are present. Inside the petrochemical area also operated, from 195… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…The original environment was also modified over time by sediment dredging within the port and its relative settlement in both legal and illegal disposal offshore areas (Bellucci et al ., ). Thus, much of the literature is also focused on the effects of industrial activity and its relative contaminant influence on the coastal ecosystem as a whole (Decembrini et al ., ; Raffa & Hopkins, ), and especially on the living benthic foraminiferal communities based on data from shallow cores and box‐core stations within the harbour (Romano et al ., , , ; Bergamin & Romano, ), and from the outer shelf in the southern part of Augusta Bay (Di Leonardo et al ., ).…”
Section: Study Sitementioning
confidence: 97%
“…The original environment was also modified over time by sediment dredging within the port and its relative settlement in both legal and illegal disposal offshore areas (Bellucci et al ., ). Thus, much of the literature is also focused on the effects of industrial activity and its relative contaminant influence on the coastal ecosystem as a whole (Decembrini et al ., ; Raffa & Hopkins, ), and especially on the living benthic foraminiferal communities based on data from shallow cores and box‐core stations within the harbour (Romano et al ., , , ; Bergamin & Romano, ), and from the outer shelf in the southern part of Augusta Bay (Di Leonardo et al ., ).…”
Section: Study Sitementioning
confidence: 97%
“…The contamination could be as a result of industrial activities, discharge of waste containing hydrocarbon and its contents. High level of contamination of polycyclic aromatic hydrocarbon in marine coastal area caused by industrial, petrochemical plants effluent, agricultural runoffs and navigation waste discharges were also reported by researchers [29,30,31]. The polycyclic aromatic hydrocarbon in the treated options reduced progressively in all the days.…”
Section: Discussionmentioning
confidence: 56%
“…Here, industrial activities started in the late 1950s and caused progressive contamination of the environment over the years. Previous studies have reported high contamination in the marine environment [17,[78][79][80][81][82], showing severe metal (Cd, Cr, Cu and Hg), PCBs and PAHs contamination. Nevertheless, terrestrial organisms, such as the ground beetle (Parallelomorphus laevigatus) or the sandhopper (Talitrus saltator) living in the Magnisi peninsula, or on the nearby beach of Marina di Priolo, did not show critical concentrations of trace elements when compared with other Sicilian areas [83,84], with the exception of Pb and Hg bioaccumulation in Ligia italica [85].…”
Section: Discussionmentioning
confidence: 97%